EFEKTIVITAS WORKSHOP AUGMENTED REALITY MENGGUNAKAN ASSEMBLR EDU DALAM MENINGKATKAN KOMPETENSI TEKNOLOGI PEDAGOGIS GURU - Wilda Fitria Nurliani; Annida Salsabila; Mei Rani Anjali Hutahaean; Tamara Yasmine Septiana Tyaskinanthi; Zahra Sherina Hayati; Gia Nikawanti; Carmelia Atin Supriatin; Sisilia Denok Sulistiarini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effectiveness of an Augmented Reality workshop using Assemblr Edu in improving teachers’ technological pedagogical competence. Teachers at Yos Sudarso School experienced limitations in accessing technology-based training, resulting in low integration of digital media in learning. This study employed a quasi-experimental one-group pretest–posttest design involving seven teachers. Data were collected using a validated questionnaire measuring four competence dimensions: cognitive, technical skills, affective, and pedagogical-technological competence. Data analysis was conducted using paired sample t-test and descriptive statistics. The results showed a significant improvement in the cognitive dimension (p = 0.040) with an increase of 30.2%. Technical skills increased by 27.6% but were not statistically significant. The affective dimension remained high and stable, while pedagogical-technological competence showed minimal change. These findings indicate that short-duration workshops are effective in strengthening teachers’ conceptual understanding of Augmented Reality; however, the development of pedagogical-technological competence requires sustained training and implementation mentoring